(untitled) (Research, Society and Development, 2020)
In Brazil, in general, milk is obtained in deficient hygienic-sanitary conditions, consequently, it presents a high number of contaminating microorganisms. Microbial growth in milk causes great economic damage to the processing industries. Fungi play an important role in the dairy industry, as they can promote deterioration or trigger undesirable fermentation and / or maturation to milk derivatives. The present study aimed to investigate the relationship between total bacterial count (TBC) and the isolation of filamentous fungi and yeasts in milk samples from the expansion tank. Milk from 160 farms was monitored for 6 months for somatic cell count (SCC) and TBC by official methods. Samples of 120 properties were analyzed for TBC and fungal isolation. In 102 samples (85%) filamentous fungi (Acremonium sp., Alternaria spp., Aspergillus sp., Cladosporium sp., Fusarium sp., Mucor spp., Penicillium sp.) and / or Candida sp., Geotrichum sp., Pichia sp., Prothoteca sp., Rodothorula sp., Trichosporon sp.) with an average of 1,284 UFC/mL and TBC of 133,000 UFC/mL. In 14 negative samples for fungi, an average of 652,000 CFU/mL was obtained for TBC. The difference in TBC between positive and negative samples for fungi was significant (p <0.001), demonstrating the influence of fungi on bacterial growth and milk TBC. The presence of fungi and the potential risk of toxin production in raw milk and its derivatives should be investigated, as well as the relationship between fungal isolation and low milk TBC.